FEATURES OF MIXED TYPE OF ECONOMIC SYSTEM IN CHINA - Yusyp O.L., (Pressing Problems of Public Administration, 2016)
The paper presents a general characteristic of the mixed economic system and determines thespecificity of its organization in the process of reforming the economy of China.